2014
DOI: 10.1016/j.cub.2014.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Cdk1 Inactivation Terminates Mitotic Checkpoint Surveillance and Stabilizes Kinetochore Attachments in Anaphase

Abstract: SummaryTwo mechanisms safeguard the bipolar attachment of chromosomes in mitosis. A correction mechanism destabilizes erroneous attachments that do not generate tension across sister kinetochores [1]. In response to unattached kinetochores, the mitotic checkpoint delays anaphase onset by inhibiting the anaphase-promoting complex/cyclosome (APC/CCdc20) [2]. Upon satisfaction of both pathways, the APC/CCdc20 elicits the degradation of securin and cyclin B [3]. This liberates separase triggering sister chromatid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 30 publications
5
74
0
Order By: Relevance
“…Nonetheless, stabilized cyclin B allowed checkpoint proteins to relocalize to kinetochores upon anaphase onset, as had been previously observed 25,26,28,29,111,134,137 . This indicated that loss of tension at anaphase does indeed promote checkpoint signaling, but this response is normally repressed by Cdk1 inactivation.…”
Section: The Checkpoint At the Limitssupporting
confidence: 68%
See 2 more Smart Citations
“…Nonetheless, stabilized cyclin B allowed checkpoint proteins to relocalize to kinetochores upon anaphase onset, as had been previously observed 25,26,28,29,111,134,137 . This indicated that loss of tension at anaphase does indeed promote checkpoint signaling, but this response is normally repressed by Cdk1 inactivation.…”
Section: The Checkpoint At the Limitssupporting
confidence: 68%
“…Several additional studies have analyzed the anaphase response further by using non-degradable cyclin B, the cofactor that activates Cdk1 towards its mitotic targets, in fission yeast 25 , mice 27 , and human cells 26,28 Stabilizing cyclin B permitted securin degradation and sister chromatid separation with a corresponding loss of kinetochore tension 25-28 . Nonetheless, stabilized cyclin B allowed checkpoint proteins to relocalize to kinetochores upon anaphase onset, as had been previously observed 25,26,28,29,111,134,137 .…”
Section: The Checkpoint At the Limitsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,18,19 Therefore, subsequently we asked to which degree cyclin B1 must be removed in order to prevent spindle checkpoint re-activation in anaphase. We filmed cells expressing a new cyclin B1 mutant, Δ52-85-cyclin B1, which has a deletion within a lysine-rich region that we noticed to be conserved downstream of the D-box ( Fig.…”
Section: Apc/cmentioning
confidence: 99%
“…The problem appears to be avoided by the timely inactivation of Cdk1 prior to anaphase, in metaphase. [10][11][12][13][14][15] It is unknown at the moment whether the anaphase problem could occur naturally, or may contribute to aneuploidy in cases when Cdk1 regulatory factors are abnormally expressed. How inactivation of Cdk1 prevents the anaphase problem is also still largely unclear.…”
mentioning
confidence: 99%